(untitled) (Research, Society and Development, 2022)
Among the invertebrates, insects make up the group that can identify the largest adaptive irradiation to the known terrestrial environment, enjoy practically all types of habitats, presenting ample adaptive plasticity. These animals are very important for maintaining organic matter cycles and success in the energy flow of terrestrial ecosystems. The problem is that, due to the reduction of food sources and nesting sites, the intensive occupation of land and the use of agricultural pesticides, wild insect populations have been drastically reduced, putting at risk the entire biome in which they live. The objective of this work was to perform a survey of the entomological diversity of a rural property in lower São Francisco - SE, using pitfalls traps. The work was carried out from April to May 2020 in the village of São Tiago, municipality of Telha. A total of 115 insects were captured, the sampled animals were classified at family level. The use of pitfalls traps for the sampling of insects in this anthropized area proved to be a tool capable of contributing to the collection of data on the abundance of individuals of the entomofauna.